2002
DOI: 10.1001/archpsyc.59.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Parental Major Depression and the Risk of Depression and Other Mental Disorders in Offspring

Abstract: Major depression in parents increases the overall risk in offspring for onset of depressive and other mental disorders and influences patterns of the natural course of depression in the early stages of manifestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
341
3
15

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 451 publications
(394 citation statements)
references
References 58 publications
35
341
3
15
Order By: Relevance
“…42 The association between parental anxiety and disease management is an important area that needs further study. Another important issue is the familial pattern of symptoms of anxiety, as in general psychopathological symptoms are likely to aggregate in families 43,44 and thus, it is possible that anxious symptoms in caregivers beget anxious symptoms in the child or vice versa. We addressed this issue in a separate paper on symptoms of psychological distress in parent-child dyads which is currently under review.…”
Section: Discussionmentioning
confidence: 99%
“…42 The association between parental anxiety and disease management is an important area that needs further study. Another important issue is the familial pattern of symptoms of anxiety, as in general psychopathological symptoms are likely to aggregate in families 43,44 and thus, it is possible that anxious symptoms in caregivers beget anxious symptoms in the child or vice versa. We addressed this issue in a separate paper on symptoms of psychological distress in parent-child dyads which is currently under review.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary to the findings of studies where offspring are the affected proband, investigations of depressed parents and grandparents have also found increased risk of anxiety (Lieb et al 2002a ;Weissman et al 2005), depression and substance disorders in offspring (e.g. Lieb et al 2002a).…”
Section: Familialitymentioning
confidence: 91%
“…Lieb et al 2002a). The inter-cluster familiality of some of the emotional disorders and some of the externalizing disorders may be explained by common genetically determined vulnerability or by social learning within families.…”
Section: Familialitymentioning
confidence: 99%
“…Our study adds to the existing evidence in that we were able to account for a range of lifetime factors which could explain associations between early behaviour and ecstasy use, but which had never been accounted for in the literature before. We adjusted for maternal depression and anxiety, which have been found to be associated with children's problem behaviour and substance abuse disorders ( [Alati et al, 2005] and [Lieb et al, 2002a]), and maternal alcohol and tobacco use, and found that these only mildly reduced the strength of the association between delinquent and aggressive behaviour and ecstasy use. Further, this is the first study able to take into account the effect of early use of alcohol and tobacco and the first study to suggest that early experimentation with these licit drugs may explain at least some of the relationship between externalising behaviour in adolescence and later ecstasy use.…”
Section: Strengths Of the Studymentioning
confidence: 99%
“…The authors also found an 81% increase in risk of ecstasy use among those reporting delinquent behaviour in childhood, raising the possibility that another pathway, common to the development of use of other drugs, may also be at play in the development of ecstasy use disorders (King et al, 2004). This may involve an indirect pathway from parental anxiety and depression (Lieb et al, 2002a), to exposure to parental use of tobacco and alcohol (Alati et al, 2005), to children's behavioural problems and early use of licit substances (King et al, 2004). These life course factors are known to predict substance use in youth (Alati et al, 2005), but their influence on regular ecstasy use in particular awaits investigation.…”
Section: Introductionmentioning
confidence: 96%